2013
DOI: 10.1001/jamadermatol.2013.1434
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Significance of Anti–Laminin 332 Autoantibodies Detected by a Novel Enzyme-Linked Immunosorbent Assay in Mucous Membrane Pemphigoid

Abstract: Importance:A rare variant of mucous membrane pemphigoid (MMP) is characterized by circulating antilaminin 332 (Lam332) autoantibodies and seems to be associated with concurrent malignant neoplasms.Objective: To determine the prevalence and clinical significance of anti-Lam332 autoantibody detection from a large series of patients with MMP.Design: Multicenter retrospective study. Interventions: Serum samples were analyzed by a new Lam332 enzyme-linked immunosorbent assay (ELISA); clinical and immunopathologic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
4
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 51 publications
(75 reference statements)
6
90
4
4
Order By: Relevance
“…IgG antibodies to laminin‐332 are detected in some MMP patients, but not in BP patients . Previous studies of IgG reactivity against laminin‐332 demonstrated positivity in 20% of MMP patients, with no association with a distinct clinical phenotype . However, they additionally did not demonstrate an association with malignancy which was later identified by the specific study of laminin 332‐reactive MMP patients .…”
Section: Introductionmentioning
confidence: 92%
“…IgG antibodies to laminin‐332 are detected in some MMP patients, but not in BP patients . Previous studies of IgG reactivity against laminin‐332 demonstrated positivity in 20% of MMP patients, with no association with a distinct clinical phenotype . However, they additionally did not demonstrate an association with malignancy which was later identified by the specific study of laminin 332‐reactive MMP patients .…”
Section: Introductionmentioning
confidence: 92%
“…Various other ELISAs have been reported, including those for detection of IgE antibodies against BP180 NC16A and for detection of serum reactivity against desmocollins , laminin γ1 , the ectodomain of BP180 , full‐length BP180 , laminin 332 , and various other forms of BP180 . Some recent ELISA systems have not yet been standardized and are only available in specialized laboratories.…”
Section: Enzyme‐linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Außerdem wurden verschiedene weitere ELISAs beschrieben, unter anderem für den Nachweis von IgE‐Antikörpern gegen BP180 NC16A und den Nachweis einer Serumreaktivität gegen Desmocolline , Laminin γ1 , die Ektodomäne von BP180 , das BP180‐Gesamtprotein , Laminin 332 und verschiedene andere Formen von BP180 . Einige der neu entwickelten ELISA‐Systeme sind noch nicht standardisiert und stehen nur in Speziallaboratorien zur Verfügung.…”
Section: Elisa (Enzyme‐linked Immunosorbent Assay)unclassified